In silico evaluation of the role of Fab glycosylation in cetuximab antibody dynamics - Saporiti, Simona; Bianchi, Davide; Ben Mariem, Omar; Rossi, Mara; Guerrini, Uliano; Eberini, Ivano; Centola, Fabio (Frontiers in Immunology, 2024)
Introduction: N-glycosylation is a post-translational modification that is highly important for the development of monoclonal antibodies (mAbs), as it regulates their biological activity, particularly in terms of immune effector functions. While typically added at the Fc level, approximately 15-25% of circulating antibodies exhibit glycosylation in the Fab domains as well. To the best of our knowledge, cetuximab (Erbitux®) is the only therapeutic antibody presenting Fab glycosylation approved worldwide targeting the epidermal growth factor receptor for the treatment of metastatic-colorectal and head and neck cancers. Additionally, it can trigger antibody-dependent cell cytotoxicity (ADCC), a response that typically is influenced by N-glycosylation at Fc level. However, the role of Fab glycosylation in cetuximab remains poorly understood. Hence, this study aims to investigate the structural role of Fab glycosylation on the conformational behavior of cetuximab.The study was performed in silico via accelerated molecular dynamics simulations. The commercial cetuximab was compared to its form without Fab glycosylation and structural descriptors were evaluated to establish conformational differences.The results clearly show a correlation between the Fab glycosylation and structural descriptors that may modulate the conformational freedom of the antibody, potentially affecting Fc effector functions, and suggesting a negative role of Fab glycosylation on the interaction with FcγRIIIa. Conclusion: Fab glycosylation of cetuximab is the most critical challenge for biosimilar development, but the differences highlighted in this work with respect to its aglycosylated form can improve the knowledge and represent also a great opportunity to develop novel strategies of biotherapeutics.